2010
DOI: 10.1016/j.brainresbull.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic keratopathy and treatment by modulation of the opioid growth factor (OGF)–OGF receptor (OGFr) axis with naltrexone: A review

Abstract: The Opioid Growth Factor (OGF) -OGF receptors (OGFr) axis plays an important role in the homeostasis and re-epithelialization of the mammalian cornea. This tonically active growth regulatory inhibitory pathway is involved in cell replication, and the endogenous neuropeptide OGF targets cyclin dependent kinase inhibitors, p16 and/or p21. Blockade of OGF-OGFr interfacing by systemic or topical administration of opioid antagonists such as naltrexone (NTX) results in accelerated DNA synthesis, cell replication, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 122 publications
1
40
0
Order By: Relevance
“…It was commented that oxidative stress has been described in human and animal diabetic corneas (28).…”
Section: Discussionmentioning
confidence: 99%
“…It was commented that oxidative stress has been described in human and animal diabetic corneas (28).…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic signs of DK are dry eye, delayed corneal wound repair, and impaired corneal nerve sensation. [28][29][30] DK was estimated to affect 49%-60% of diabetic patients. 29 Naltrexone is a wellknown opioid antagonist and it is commonly used for treatment of opioid dependence and alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 One native opioid peptide, MENK, has emerged as a modulator on several immunological functions both in vitro and in vivo such as enhancing the proliferation of peripheral blood lymphocytes and splenocytes. 30 MENK possesses bilateral regulation on immune cells, which means that MENK at higher concentrations such as 10 -6 M or lower concentrations such as 10 -18 M will delay immune cell growth and the possible mechanism is MENK can interact with OGFr to upregulate cyclin-dependent kinase inhibitory (CKI) pathways and markedly delay the G 1 /S phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…27,[40][41][42] PTD, a synthetic substance, has been shown to ameliorate different functions of innate and adaptive immune responses both in animals and humans. 28 It has been reported that PTD was able to enhance the effectors of the innate immunity responses by potentiating different functions of the professional phagocytes and NK cell activity; PTD also significantly increased the proliferation of spleen cells in response to Con-A and interleukin-2 (IL-2) stimulation. 28,43 On the other hand, large clinical trials have been conducted on patients shown that PTD displayed a beneficial activity in recurrent upper respiratory and urinary tract to which the innate immune system vigorously reacts, resulting in a generalized potentiation of the immune system so that the Ag coadministered with adjuvant can be taken up more effectively, processed and presented by activated DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation